The Role of Parents' Socio-Economic Conditions Against Mathematics Learning Outcomes of Madrasah Ibtidaiyah Students - Anna Fista Nugraheni; Avita Febri Hidayana (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2019)
One of the factors that influence children's development is the parents' socioeconomic status. Some students are revealed to have mathematics learning outcomes that have not yet reached the Minimum Mastery Criteria (Kriteria Ketuntasan Minimal or KKM).  It might occur due to the economic conditions of parents.  Therefore, the researchers desired to determine the effect of parents' socioeconomic status on the learning outcomes of students in the fifth-grade of the Madrasah Ibtidaiyah (Islamic Elementary School or MI) Islamiyah Karangpakel.  The purpose of this study was to determine the effect of parents' socioeconomic status on student mathematics learning outcomes at Islamiyah Karangpakel.  Questionnaires and documentation were used as data collection techniques.  The study was conducted by quantitative methods with the type of expost de facto.  The study population consisted of students in the fifth grade of MI Islamiyah Karangpakel, with a total of 20 students.  The data analysis technique used Simple Linear Regression and was assisted by SPSS 16.0.  Based on the calculation of the significance level of 5%, it indicates that the influence of parents' socioeconomic status on student mathematics learning outcomes was in precentage 41,4%, or has sufficient influence while other variables or factors influence the rest.  Thus, it can be concluded that the influence of parents' social economic status influences students’ mathematics learning outcomes.